The Effect of Perceptions of Job Characteristics on the Components of the Organizational Commitment of Civil Servants in the Serdang District Government is Different - Firstiani, Elsa (Acta Psychologia, 2022)
This study aims to see the effect of perceptions of job characteristics on the three components of organizational commitment in the civil servants of the Serdang Bedagai Regency Government. This district is one of the new districts in Indonesia and was the best new district in 2008. However, the performance of civil servants in this district is still not good. The results of data analysis using linear regression analysis technique show that the linear equation for the perception variable regarding job characteristics and affective commitment is Y = 12.221 + 0.109X, and the coefficient of determination is 0.118. This shows that perceptions of job characteristics contribute effectively to 11.8% of employees' affective commitment. For the variable perception of job characteristics and commitment to continuity, the resulting line equation is Y = 13,197 + 0.078X, and the coefficient of determination is 0.038. This shows that the perception of the characteristics of the job provides an effective contribution of 3.8% to employee continuance commitment. For the perception variable regarding job characteristics and normative commitment, the resulting line equation is Y = 14,639 + 0.067X, and the coefficient of determination is 0.37. This shows that the perception of the characteristics of the job provides an effective contribution of 3.7% to employee continuance commitment.